(untitled) (International Journal of Architecture and Urbanism, 2025)
The global outbreak of COVID-19 since 2019 has caused significant losses, profoundly affecting socio-economic development and altering human lifestyles. This paper examines the challenges faced by Tanzhou Vegetable Market in Zhongshan City, China, during the pandemic and proposes a transformation design for the market. The study utilizes a combination of literature review and field research methods to identify issues and develop solutions. The primary focus includes analyzing the existing problems at Tanzhou Vegetable Market, presenting the necessary transformation strategies for epidemic prevention, and detailing the design changes required. The renovation involves improving the market’s external environment with modifications to the entrances, traffic flow, and the addition of green spaces. Internally, the design reorganization addresses functional layout, internal traffic flow, and the arrangement of stalls. The transformed market successfully integrates modern aesthetics and epidemic control measures while maintaining its core function as a space for vegetable transactions. The result is a more user-friendly, secure, and pleasant environment for the public. This study provides a practical framework for transforming other urban vegetable markets in the post-epidemic era.